Aplikasi Metode Work Study pada Proyek Konstruksi (Studi Kasus Rusunawa LANUD TNI AU Adi Sutjipto Yogyakarta) - Priyo, Mandiyo; Nasrudin, Gayuh Agus (Jurnal Semesta Teknika, 2014)
Work study method is one of the management approach that use for study about the productivity of workers. Work study can be applied in many cases, one of which is the construction of Rusunawa TNI AU Lanud Adi Sutjipto Yogyakarta. Chosen plant project Rusunawa TNI AU Lanud Adi Sutjipto Yogyakarta because this project uses a system of precast concrete in construction. Precast concrete systems is still quite rarely used in Yogyakarta so that this is makes the researchers reviewed the project to study the case. This study aimed to compare the time between installation plan (time schedule) and the actual installation time also to know the time clean installation of structural elements. In addition, this study also aims to determine the cost of erection of a single structural element. This study utilizes the basic time data by consider relaxation allowance and contingences for the purpose to eliminate subjectivity in assessing both. Basic recording time is using a stopwatch. Whereas the standard time value can be from basic time coupled with relaxation allowance and contingences. The results of this study have shown that the value of the standard time for the installation of columns, beams and plates is 13.63163 minutes; 8.505156 minutes; 8.465704 minutes. Obtained also the cost of erection of columns, beams and slabs of Rp 24629.96; Rp 15710.91; Rp 15710.91.